Indigenous surgical practices in rural southwestern Nigeria: implications for disease prevention (1995)
A qualitative, community-based study was conducted in the rural community of Ago Are in southwestern Nigeria to learn about indigenous surgical practices and their potential for disease transmission. Community leaders as key informants assisted in identifying two types of indigenous practitioner whose work involved blood contact, whose work was observed. The olola are surgeons who specialize in circumcision and making traditional facial-markings, while the generic term for healer, onisegun, performed gbeere, that is making incisions into which medicinal herbs are rubbed. Although the onisegun used a clean blade for his procedures, he rubbed the herbs into the cuts with his bare hands. The olola used the same knife for all operations and cleaned it simply by rinsing it in a bowl of water. The potential for HIV transmission between practitioner and clients and among clients during these procedures is discussed-as is the potential of health education for reducing the demand for female circumcision and training indigenous healers in hygienic methods.